Myth employment in the short story Mythic Critical Study in Sana Saalan story last citizen - Kohaili, Wanassa (Milev Journal of Research and Studies, 2021)
Heritage employment is one of the most important topics that have been and are still of interest to many critics and scholars - because of its clear impact on shaping the aesthetics of the discourse - as they used folklore to employ it and draw inspiration from it that suits their subjects, differing in how they employ it in terms of form and content; or the so-called expressive form and content, and some of them employ it in a symbolic way as a kind of disguise or coverage of a topic. With reference to contemporary literary works, we find that the most used and employed heritage form of expression is the myth, as it was an inexhaustible source for all writers and an effective means of .expressing the feelings of desire to revolt against the living reality, prevailing values, and corrupt systems